2023
DOI: 10.1021/acs.langmuir.3c02055
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Dielectric Properties of PVDF–HFP/SrTiO3 Nanocomposites for a Flexible Film Capacitor

Subhasree Panda,
S. K. Khadheer Pasha

Abstract: A simple solution casting technique was used to fabricate perovskite strontium titanate (SrTiO3)-loaded poly(vinylidenefluoride-co-hexafluoropropylene) (PVDF–HFP) nanocomposite films for efficient energy storage applications. Various microscopic and spectroscopic methods were used to study the characteristics of the polymer nanocomposite films, like Fourier transform infrared spectroscopy (FTIR), X-ray diffraction technique (XRD), field emission scanning electron microscopy (FESEM), ultraviolet–visible spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Nevertheless, the recorded tensile strength and elongation at break values for the P(VDF‐HFP) film filled with 3 wt% CaCl 2 ·6H 2 O exceeded those of the pure P(VDF‐HFP) film, with respective values of 11.9 MPa and 260%, as reported by Panda and Pasha 60 . Furthermore, the reduction in these values within the composites significantly enhances film flexibility, facilitating easy deformation under applied force.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Nevertheless, the recorded tensile strength and elongation at break values for the P(VDF‐HFP) film filled with 3 wt% CaCl 2 ·6H 2 O exceeded those of the pure P(VDF‐HFP) film, with respective values of 11.9 MPa and 260%, as reported by Panda and Pasha 60 . Furthermore, the reduction in these values within the composites significantly enhances film flexibility, facilitating easy deformation under applied force.…”
Section: Resultssupporting
confidence: 57%
“…Subsequently, the curve transitions from elastic to plastic deformation, reaching a yield point where plastic deformation occurs. The stress value at the fracture point, representing a polymer's ability to withstand a pulling force, defines the tensile strength for the P(VDF‐HFP) copolymer 60,61 . Analyzing Table 2 reveals that the Young's modulus value in the elastic region, derived from Equation (3), decreases with an increase in calcium salt concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The most popular high-k and lead-free materials are BaTiO 3 [145], SrTiO 3 [146,147], Ba/SrTiO 3 [137,148], and BiFeO 3 [149]. Wen et al reported BT/PVDF composites using 2D platelets, which were prepared and investigated in this work (Figure 11a-d) [20].…”
Section: Lead-free Ceramicsmentioning
confidence: 96%